A Theoretical Feature-wise Study of Malware Detection Techniques - Samantray, Om Prakash; Tripathy, Satya Narayana; Das, Susant Kumar (International Journal of Computer Sciences and Engineering, 2018)
Malware is the acronym of Malicious Software. It has become a big threat in today’s computing world. The threat is increasing with a greater pace as the use of Internet in our day to day activities is growing extensively. The number of malware creators and websites distributing malware is increasing at an alarming rate which attracts researchers and developers to develop a better security solution for it. Developing an efficient malware detection technique is still an ongoing research. Understanding malware, features of malware, analysis methods and detection techniques are the prerequisites of malware research. In this paper, we have studied a few past research works based on API calls, N-Grams, Opcodes features used in malware detection. A detailed fundamental concept of malware detection is also presented in this paper. Use of Data mining algorithms in malware detection, different types of malware detection and analysis methods along with their pros and cons are also presented here. Aim of this paper is to gain prerequisite knowledge of malware research and concepts of malware detection techniques.